Endometriosis fertility index at laparoscope: a ray of hope and lots of scope - Kavya, Vemparala Kalabhashini; Palanisamy, Sindhuja T.; Palaniappan, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Endometriosis fertility index (EFI) is used to predict the fecundity in women with surgically and histologically confirmed endometriosis. Aim of the study is to evaluate the successful spontaneous pregnancy rates in patients with endometriosis after laparoscopic surgery in relation to EFI score. Methods: Observational cross-sectional study was conducted on 76 patients who desire to conceive with suspected endometriosis related infertility treated by laparoscopic surgery. EFI score was calculated and information on mode of conception (spontaneous or assisted reproductive technology-ART) was collected by contacting the patients. Results: In women who conceived spontaneously, mean age was 31.33+3.29 years. Factors found to be significant were age (pvalue-0.0001), time to achieve spontaneous pregnancy (median-9 months). Patients with higher EFI score (5-10) has good spontaneous conception rate (96.2%) compared to those with lower EFI score (0-4) that conceived better with ART (60%) women with lower least function score has better outcome for spontaneous pregnancy (p<0.001). Conclusions: EFI scoring system is effective in predicting postoperative successful spontaneous pregnancy rates in the patients with endometriosis. In our study patients with higher EFI score achieved successful spontaneous pregnancy.